A study to analyses the clinical features and various treatment modalities of varicose veins of lower limbs - Nayak, Santosh; M. S., Parthiban (International Surgery Journal, 2018)
Background: Varicose veins are defined by WHO as abnormally dilated saccular or cylindrical superficial veins, which can be circumscribed or segmental. This includes tiny spider telangiectasia’s as well as grossly dilated saphenous varicosities. It involves at least 1 out of 5 in the world and with increasing population, increased life span and change in life style, the problem is ever growing. The objective of this study is to analyse the clinical features and various treatment modalities adopted for the management of varicose veins of 40 has some form of varicosity or telangiectasia of the veins. Methods: A prospective study was conducted in CG hospital and Bapuji hospital attached to JJM Medical College, Davangere from June 2009 to May 2011. A total of 40 cases were included in the study duration. All patients who presented to the outpatient department with signs and symptoms of primary varicose veins were interviewed with preformed performa, meticulously examined and later subjected to color doppler studies before they underwent surgery for the same. Results: The incidence of varicose veins was seen most commonly in male when compared to female in this study. The family history of varicose veins was seen in only 12.5% of the subjects. In this study patients presented with varied symptoms, out of which dilated veins was most common 37 (92.5%) patients followed by aching pain 22 patients (55%). Conclusions: Varicosity of the lower limb is a common clinical entity. The number of cases reporting to the hospital is much less than the real incidence because in the absence of symptoms due to varicose veins patients do not seek treatment in our country. Most of the patient presented to the hospital for one or the other complications not for the cosmetic purpose.